Weight status and its determinants among Moroccan adolescents in the province of El Jadida - Khadija Sahel; Abdelghani Aboukhalaf; Sanaa Eljamal; Houda Elfane; Mohammed El Ayachi; Rekia Belahsen (National Institute of Public Health - National Institute of Hygiene, 2022)
Background. Despite the efforts of health systems, the prevalence of malnutrition reflected by weight status still poses challenges for many countries around the world. In fact, with the decrease in undernutrition, excess weight and obesity are gradually increasing in parallel with that of chronic diseases. Among school-going adolescents, however, weight status is less studied, particularly in developing countries. Objective. The objective of this research is to examine the situation and the determinants of the weight status of adolescents in the province of El Jadida in Morocco. Material and methods. The study was carried out on a sample of 463 students from the province of El Jadida of which 58.1% are boys and 41.9% girls, ages 9 and 17. Nutritional status was assessed by anthropometric measurements including height, weight and waist and hip circumference. Body mass index (BMI) was calculated to determine underweight, overweight and general obesity and waist circumference and the waist circumference to hip circumference ratio were used to determine abdominal obesity. Results. The results indicate that only 59.6% of students had normal weight status, 40.4% had abnormal BMI values corresponding to thinness in 18.8% and overweight (overweight and obesity) in 21.6%. A significant difference in the prevalence of abnormal weight status by sex and level of physical activity was found. The results of the present study reveal an abnormal weight status in a large proportion of adolescents linked in addition to the peculiarities of the puberty phase to the sedentary lifestyle in the study population. Conclusions. The results obtained revealed the coexistence of over-nutrition and undernutrition which require a prevention policy based on regular monitoring of weight status as well as on nutritional education and the promotion of physical activity for children and parents.